Managerial competencies of hospital managers in South Africa: a survey of managers in the public and private sectors - Pillay Rubin (BMC, 2008)
Abstract Background South Africa has large public and private sectors and there is a common perception that public sector hospitals are inefficient and ineffective while the privately owned and managed hospitals provide superior care and are more sustainable. The underlying assumption is that there is a potential gap in management capacity between the two sectors. This study aims to ascertain the skills and competency levels of hospital managers in South Africa and to determine whether there are any significant differences in competency levels between managers in the different sectors. Methods A survey using a self administered questionnaire was conducted among hospital managers in South Africa. Respondents were asked to rate their proficiency with seven key functions that they perform. These included delivery of health care, planning, organizing, leading, controlling, legal and ethical, and self-management. Ratings were based on a five point Likert scale ranging from very low skill level to very high skill level. Results The results show that managers in the private sector perceived themselves to be significantly more competent than their public sector colleagues in most of the management facets. Public sector managers were also more likely than their private sector colleagues to report that they required further development and training. Conclusion The findings confirm our supposition that there is a lack of management capacity within the public sector in South Africa and that there is a significant gap between private and public sectors. It provides evidence that there is a great need for further development of managers, especially those in the public sector. The onus is therefore on administrators and those responsible for management education and training to identify managers in need of development and to make available training that is contextually relevant in terms of design and delivery.